ASSESSING THE INFLUENCE OF THIN CAPITALIZATION AND FISCAL LOSS COMPENSATION ON TAX AVOIDANCE IN THE INDONESIAN MANUFACTURING SECTOR - G, Taylor; G, Richardson, (Economics and Statistics Research Journal (ESRJ), 2023)
This study investigates the impact of thin capitalization and fiscal loss compensation on tax avoidance in Indonesian manufacturing companies. It aims to provide insights into the factors influencing tax avoidance and to enhance tax avoidance rules in the manufacturing industry in Indonesia to improve government tax income. Secondary data in the form of financial reports and annual reports of 30 purposively sampled manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021 were analyzed using multiple regression methods. The study found that thin capitalization and fiscal loss compensation have a significant impact on tax avoidance in Indonesian manufacturing companies. However, transfer pricing aggressiveness and political connections did not have a significant effect on tax avoidance. Positive Accounting Theory and Tax Avoidance were reviewed as theoretical frameworks, and descriptive statistical analysis, normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test were performed to test the research hypotheses. The findings of this study can help policymakers and companies to better understand the negative impact of tax avoidance on government income and to implement measures to reduce tax avoidance in the manufacturing industry in Indonesia